Epidemiological surveillance of endogenous and exogenous nosocomial infections (Annals of Medical Research, 2021)
Aim: Nosocomial infections (NIs) represent a major public health problem in developed, and even more in developing countries. Based on the origin of the pathogen, NIs are divided into endogenous caused by microorganisms of the patient’s microflora, and exogenous caused by pathogens from the patient’s environment or by the same microorganism isolated elsewhere from patient’s body. The main aim of this research was to determine the frequency, etiology and types of NIs at the Clinic for Surgery of the University Clinical Center Tuzla. Material and Methods: 5.039 patients were prospectively followed for the development of endogenous and exogenous NIs (January-December 2015). The definition of NI was performed using standardized the National Healthcare Safety Network (NHSN) criteria.Results: Based on continuous epidemiological surveillance, the incidence of NI was 3.51%; with a total of 177 registered infections, 24 endogenous and 153 exogenous. The most common NIs were urinary tract infections (UTIs) (14.29% endogenous and 85.71% exogenous) and surgical site infections (SSIs) (16.67% endogenous and 83.33% exogenous), p0.001. Gram-negative bacteria were predominant (76.84%) over Gram-positive bacteria (23.16%). Gram-positive bacteria mainly caused bacteremia, while Gram-negative bacteria were most commonly isolated from UTIs and SSIs. The most common Gram-negative bacteria were Klebsiella pneumoniae (24.86%) and Pseudomonas aeruginosa (22.6%), and among Gram-positive, Staphylococcus aureus (10.73%) and coagulase-negative staphylococci (7.91%).Conclusion: Epidemiological surveillance is considered a key link in the program for the prevention and control of NIs. The most important, and the ultimate goal and purpose of conducting epidemiological surveillance are to reduce and eliminate the risk factors, which can lead to a reduction in NI incidence rate. Determining the endemic rates of NIs provides an objective understanding of the overall NI status in an institution as well as existing risk factors for the occurrence of these infections.